Posterior Fossa Tumors in Children - Özek, M. Memet; Cinalli, Giuseppe; Maixner, Wirginia; Sainte-Rose, Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book, written by experts from across the world, provides a comprehensive, up-to-date overview covering all aspects of pediatric posterior fossa tumors, including medulloblastoma, ependymoma, cerebellar astrocytoma, atypical teratoid/rhabdoid tumor, chordoma, brain stem tumors, and rarer entities. For each tumor type, individual chapters are devoted to genetics, radiological evaluation using advanced imaging techniques, surgery, pathology, oncology, and radiation treatment. In addition, a separate section describes the various surgical approaches that may be adopted and offers guidance on the treatment of hydrocephalus and the role of intraoperative mapping and monitoring. Useful information is also provided on anatomy, clinical presentation, neurological evaluation, and molecular biology. The book closes by discussing in detail immediate postoperative care, the management of surgical complications, and longer-term rehabilitation and support.   Posterior fossa tumors are the most common pediatric brain tumors but are often difficult to treat owing to their proximity to critical brain structures and their tendency to cause marked intracranial hypertension. Practitioners of all levels of experience will find Posterior Fossa Tumors in Children to be a richly illustrated, state of the art guide to the management of these tumors that will serve as an ideal reference in clinical practice.  .
Preface -- I General Principles of Treatment in Pediatric Posterior Fossa Tumors -- 1 History of Posterior fossa tumor surgery -- 2 Development of posterior fossa structures -- 3 Microsurgical anatomy of posterior fossa -- 4 Anatomical connections of cerebellum -- 5 Clinical presentation and neurological evaluation: Neuro-ophthalmology -- 6 Molecular biology -- 7 Radiation oncology -- II Surgical Approaches to Pediatric Posterior Fossa Tumors -- 8 Median suboccipital approach -- 9 Paramedian approach -- 10 Skull base approaches in children -- 11 Anterior skull base approaches to posteror fossa -- 12 Treatment of hydrocephalus in PFT -- 13 Intraoperative mapping and monitorisation of PFT -- III Pathologies in Pediatric Posterior Fossa Tumors -- i. Medulloblastoma -- 14. Genetics of PFT -- 15 Radiology in Medulloblastoma -- 16 Surgery in Pediatric Medulloblastoma -- 17 Pathology in Medulloblastoma -- 18 Oncology in Medulloblastoma -- 19 Radiation in Medulloblastoma -- ii. Ependimoma -- 20 Genetics of Ependimoma -- 21 Radiology of Ependimoma -- 22 Surgery of Ependimoma – 23 Pathology of Ependimoma -- 24 Oncology of Ependimoma -- iii. Cerebellar astrocytoma -- 25 Genetics of Cerebellar astrocytoma -- 26 Radiology of Cerebellar astrocytoma -- 27 Surgery of Cerebellar astrocytoma -- 28 Pathology Cerebellar astrocytoma 29 Oncology of Cerebellar astrocytoma -- 30 Radiation in Cerebellar astrocytoma -- iv. Brain stem tumors -- 31 Radiology in Brain stem tumors -- 32 Surgery of mesenchephalon -- 33 Surgery of pontine tumors -- 34 Surgery of medulla oblongata tumors -- 35 Pathology of Brain stem tumors -- 36 Radiation in Brain stem tumors -- 37 Oncology of Brain stem tumors -- v. AT/RT -- 38 Genetics in AT/RT -- 39 Radiology in AT/RT -- 40 Surgery in AT/RT -- 41 Pathology in AT/RT -- 42 Oncology in AT/RT -- 43 Radiation in AT/RT -- vi. Chordoma -- 44 Genetics in Chordoma -- 45 Radiology in Chordoma -- 46 Pathology in Chordoma -- 47 Management of Chordomas -- vii. Rare tumors -- 48 Surgery of choroid plexsus tumors.-49 Oncology of choroid plexsus tumors -- 50 Vestibular schwannoma -- 51 Ganglioglioma -- 52 Dermoid -- 53 Epidermoid -- 54 Lhermitte Duclos -- 55 Meningioma -- IV Pre- and Postoperative Care of Pediatric Posterior Fossa Tumors -- 56 Immediate postoperative care: Germany -- 57 Immediate postoperative care:  Athens -- 58 Immediate postoperative care: Paris -- 59  Immediate postoperative care: Istanbul -- 60 Immediate postoperative care: Korea -- 61 Immediate postoperative care: Naples -- 62 Surgical complications -- 63 Postoperative vertebral column complications -- 64 Endocrinological complications in posterior fossa tumours -- 65 Rehabilitation of neurodeficits -- 66  Psychiatric support to the family and patient -- Subject Index.
Keywords: Neurosurgery; Pediatrics; Neuroradiology; Radiotherapy; Neurology .; Oncology .; Neurosurgery; Pediatrics; Neuroradiology; Radiotherapy; Neurology; Oncology